Organization Of The Modern Educational Process In The Discipline Of Digitization - Dilnoza Zaripova Anvarovna (Euro Asian Journal Publishing, 2024)
In the face of digitalization in the world, the transition of digital economic educational institutions as an organization with an important position in the intellectual development of the country, rapid changes are present in the conditions of necessary bridges. The serious digitization of all the processes that make up the modern educational system and its impact on the teaching method is studied in the next article.
Keywords: Globalisation; education system; digitalization